THE WELFARE ANALYSIS OF CORN FARMERS' HOUSEHOLDS IN THE BUFFER AREA OF THE MANDALIKA SPECIAL ECONOMIC ZONE - Hidayati, Asri; Septiadi, Dudi; Hidayanti, Anna Apriana; Febrilia, Baiq Rika Ayu (AGROTEKSOS, 2025)
The objective of this study is to: (1) Analyze the income of corn farmers in the buffer zone of the Mandalika Special Economic Zone (SEZ); (2) Assess the welfare levels of these farmers. The research was conducted in the buffer zone of the Mandalika SEZ, specifically in Mertak Village, Pujut District, Central Lombok Regency. This study employs a qualitative-descriptive research design. Data collection was carried out through interviews guided by questionnaires with 40 respondents, selected through accidental sampling. The data analysis techniques used in this study include: (1) Income analysis; (2) Household welfare level analysis. The results indicate that: (1) The average income from corn farming per planting season in the buffer zone of the Mandalika SEZ is IDR 11,928,400 per LLG or IDR 12,563,764 per hectare; (2) Based on the NTRP, Sajogyo, and BPS approaches, on average, corn farming households fall into the prosperous category. However, when considering distribution, 30% of farming households are still not prosperous according to the NTRP approach. Additionally, according to the Sajogyo criteria, 12.5% of households are categorized as poor, and 5% as extremely poor. Meanwhile, the BPS poverty analysis reveals that 47.5% of households are classified as poor.